1993
DOI: 10.1159/000113846
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Immunological Analysis of Prey-Derived Vomeronasal Stimulants

Abstract: We have isolated seven proteins from earthworm preparations that are chemoattractive to garter snakes. Three of these proteins have been purified to homogeneity: two from aqueous earthworm wash (EWW) and one from electric shock-induced earthworm secretion (ESS). One of the two highly purified proteins from EWW has a relative molecular mass of 20 kDa and contains free sulfhydryl groups that appear to play a functional role in its chemoattractivity. The other purified protein from EWW has a molecular mass of 3 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The vomeronasal system can also detect a wider variety of chemical cues than just pheromones. Snakes have long been know to use their vomeronasal system to detect prey odors (Halpern and Kubie 1980;Wang et al, 1993;Alving and Kardong, 2004) and VSN from mice have been found to respond to a wide variety of odors some of which could be considered food odors (Sam et al, 2001). Hamsters appear to detect and process odors from different species such as mice, rats and cats (Meredith and Westberry, 2004) and possibly some food odors through the vomeronasal system.…”
Section: Pheromones and The Dual Olfactory Hypothesismentioning
confidence: 99%
“…The vomeronasal system can also detect a wider variety of chemical cues than just pheromones. Snakes have long been know to use their vomeronasal system to detect prey odors (Halpern and Kubie 1980;Wang et al, 1993;Alving and Kardong, 2004) and VSN from mice have been found to respond to a wide variety of odors some of which could be considered food odors (Sam et al, 2001). Hamsters appear to detect and process odors from different species such as mice, rats and cats (Meredith and Westberry, 2004) and possibly some food odors through the vomeronasal system.…”
Section: Pheromones and The Dual Olfactory Hypothesismentioning
confidence: 99%
“…In addition to detecting pheromones, VNO neurons have been shown to respond to regular chemical odorants in vitro , but the biological significance of this activity has not been determined (Sam et al, 2001; Trinh and Storm, 2003). In reptiles, the VNO initiates a defensive response to predators and facilitates the tracking of prey (Halpern and Frumin, 1979; Miller and Gutzke, 1999; Wang et al, 1993). In mammals, the identity of kairomones and detecting sensory neurons remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The VNS of snakes has been shown to be important for mediating courtship and mating (as in mammals), aggregation, trailing of conspecifics and prey, prey attack, and ingestion. In addition, a wealth of data has accumulated on the anatomical, physiological, cellular, and molecular details of the ophidian VNS (see Halpern 1992;Jiang and Terashima, 1996;Liu et al, 1997;Luo et al, 1994;Wang et al, 1993Wang et al, , 1997. Development of the VNS is of particular interest in snakes (Holtzman, 1993).…”
Section: Introductionmentioning
confidence: 99%